Serum endocan levels in patients with stable COPD. - Pihtili, AYLİN; PIHTILI, AYLIN; BINGOL, Z; KıYAN, E (My University, 2018)
Background: Endothelial cell specific molecule-1, also called as endocan, is a dermatan sulfate proteoglycan, which is expressed by endothelial cells in alveolar walls of the lung and kidney. High endocan levels are found associated with endothelial dysfunction and inflammation. We hypothesize that endocan level is also high in COPD due to systemic inflammation and endothelial dysfunction. We aimed to investigate the expression of endocan in patients with stable COPD. Material and methods: The study included patients with COPD and control subjects. COPD patients were classified according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2017 criteria. Demographics, body mass index, smoking history, and comorbidities were recorded. Endocan levels of COPD patients and controls were compared. Results: Totally, 88 subjects (47 stable COPD patients, 41 controls) were evaluated. Endocan levels were significantly higher in COPD patients than control group (860.1±259.8 vs 647.3±316.9 pg/mL, P=0.001). There was no relationship between GOLD COPD categories and endocan levels. Also endocan levels were similar between COPD patients with or without hypoxemia. Conclusion: Serum endocan level was significantly higher in patients with stable COPD. Further studies should be performed to better understand the relationship between endocan and COPD.